Immunochemical characterization on pathological oligomers of mutant Cu/Zn-superoxide dismutase in amyotrophic lateral sclerosis. Issue 1 (December 2017) - Tokuda, Eiichi; Anzai, Itsuki; Nomura, Takao; Toichi, Keisuke; Watanabe, Masahiko; Ohara, Shinji; Watanabe, Seiji; Yamanaka, Koji; Morisaki, Yuta; Misawa, Hidemi; Furukawa, Yoshiaki
Abstract Background Dominant mutations in Cu/Zn-superoxide dismutase (SOD1 ) gene cause a familial form of amyotrophic lateral sclerosis (SOD1 -ALS) with accumulation of misfolded SOD1 proteins as intracellular inclusions in spinal motor neurons. Oligomerization of SOD1via abnormal disulfide crosslinks has been proposed as one of the misfolding pathways occurring in mutant SOD1; however, the pathological relevance of such oligomerization in theSOD1 -ALS cases still remains obscure. Methods We prepared antibodies exclusively recognizing the SOD1 oligomers cross-linkedvia disulfide bonds in vitro. By using those antibodies, immunohistochemical examination and ELISA were mainly performed on the tissue samples of transgenic mice expressing mutant SOD1 proteins and also of humanSOD1 -ALS cases. Results We showed the recognition specificity of our antibodies exclusively toward the disulfide-crosslinked SOD1 oligomers by ELISA using various forms of purified SOD1 proteins in conformationally distinct states in vitro. Furthermore, the epitope of those antibodies was buried and inaccessible in the natively folded structure of SOD1. The antibodies were then found to specifically detect the pathological SOD1 species in the spinal motor neurons of theSOD1 -ALS patients as well as the transgenic model mice. Conclusions Our findings here suggest that the SOD1 oligomerization through the disulfide-crosslinking associates with exposure of the SOD1 structural interior and is a pathological process occurring in theSOD1 -ALS cases.